2014
DOI: 10.1590/1807-3107bor-2014.vol28.0043
|View full text |Cite
|
Sign up to set email alerts
|

Apical adaptation, sealing ability and push-out bond strength of five root-end filling materials

Abstract: This study compared the fluid filtration, adaptation to the root canal walls, and the push-out bond strength of two resin-based sealers and three calcium silicate-based retrograde filling materials. Fifty maxillary canines were shaped using manual instruments and the apical portion was sectioned. Retrograde cavities of 3-mm depth were prepared. The specimens were divided into five groups (n = 10): Sealer 26 (S26); MBPc (experimental); MTA; Portland cement with 20% zirconium oxide (PC/ZO), and Portland cement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
5
12
1
4
Order By: Relevance
“…Amoroso-Silva et al (18) According to Hong et al (20), the push-out strength was improved when MTA with calcium chloride was used. The results of the present study are consistent with those of Amoroso-Silva et al (18), who found 25.35 MPa for MTA Angelus after push-out test using apical sections of roots from human teeth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Amoroso-Silva et al (18) According to Hong et al (20), the push-out strength was improved when MTA with calcium chloride was used. The results of the present study are consistent with those of Amoroso-Silva et al (18), who found 25.35 MPa for MTA Angelus after push-out test using apical sections of roots from human teeth.…”
Section: Discussionsupporting
confidence: 93%
“…Sealer 26 showed similar results to MTA-based materials. This material was used in a thicker consistency favoring its clinical application as root-end filling material (18,19). Amoroso-Silva et al (18) According to Hong et al (20), the push-out strength was improved when MTA with calcium chloride was used.…”
Section: Discussionmentioning
confidence: 99%
“…Sealer 26 has also demonstrated to prevent bacterial leakage when compared with IRM 15 . Amoroso-Silva et al 16 demonstrated that Sealer 26, MTA and calcium silicate cements were similar after analyzing sealing by fluid leakage and dentinal adaptation. In the present study, similar filling ability was observed for S26 and ZOE, and both presented higher values than MTA.…”
Section: Discussionmentioning
confidence: 99%
“…Sealer 26 (S26) is a resin-based endodontic sealer, composed of bismuth oxide, calcium hydroxide and epoxy resin, and requires higher powder/resin proportion to favor insertion into root-end cavities 13 . It has excellent sealing properties when used as rootend filling material 15 , and presents interface adaptation similar to calcium silicate-based cements 16 . Zinc oxide and Eugenol cement (ZOE) may also be used with higher powder/liquid proportion 17 , favoring its insertion into root-end cavities.…”
Section: Introductionmentioning
confidence: 99%
“…New calcium silicate-based cements have also been studied, 23,24 and some of the modified calcium silicate and resin cements under study may present the potential for clinical use. CSCM is a modified calcium silicate cement that contains mineral aggregates, additives and pigments.…”
Section: Discussionmentioning
confidence: 99%